Interstellar medium conditions in z ~ 0.2 Lyman-break analogs - Contursi, Andrea; Nielbock, Markus (Astronomy and astrophysics, 2017)
We present an analysis of far-infrared (FIR) [CII] and [OI] fine structure line and continuum observations obtained with Herschel/PACS, and 12CO(1-0) observations obtained with the IRAM Plateau de Bure Interferometer, of Lyman-break analogs (LBAs) at z ~ 0.2. The principal aim of this work is to determine the typical interstellar medium (ISM) properties of z ~ 1−2 main sequence (MS) galaxies, with stellar masses between 109.5 and 1011M⊙, which are currently not easily detectable in all these lines even with ALMA and NOEMA. We perform PDR modeling and apply different infared diagnostics to derive the main physical parameters of the far-infrared (FIR)-emitting gas and dust and we compare the derived ISM properties to those of galaxies on and above the MS at different redshifts. We find that the ISM properties of LBAs are quite extreme (low gas temperature and high density and thermal pressure) with respect to those found in local normal spirals and more active local galaxies. LBAs have no [CII] deficit despite having the high specific star formation rates (sSFRs) typical of starbursts. Although LBAs lie above the local MS, we show that their ISM properties are more similar to those of high-redshift MS galaxies than of local galaxies above the main sequence. This data set represents an important reference for planning future ALMA [CII] observations of relatively low-mass MS galaxies at the epoch of the peak of the cosmic star formation.
Gesehen am 25.09.2018